2015
DOI: 10.1007/s00265-015-1917-x
|View full text |Cite
|
Sign up to set email alerts
|

Trading or coercion? Variation in male mating strategies between two communities of East African chimpanzees

Abstract: Across taxa, males employ a variety of mating strategies, including sexual coercion and the provision, or trading, of resources. Biological market theory (BMT) predicts that trading of commodities for mating opportunities should exist only when males cannot monopolize access to females and/or obtain mating by force, in situations where power differentials between males are low; both coercion and trading have been reported for chimpanzees (Pan troglodytes). Here, we investigate whether the choice of strategy de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 96 publications
(160 reference statements)
3
43
0
Order By: Relevance
“…Animal studies of sexual conflict have focused on its more conspicuous forms, including infanticide [10,11], forced copulations [12,13], and sexual harassment [14][15][16]. Pioneering studies exploring more discreet forms of sexual coercion, such as sexual intimidation in chimpanzees (Pan troglodytes), have reported that males who direct repeated aggression toward cycling females are more likely to mate with them around ovulation [17][18][19][20]. Besides this work and some anecdotal reports [7,21,22], the prevalence and evolutionary importance of sexual intimidation in wild primates remain largely unknown.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal studies of sexual conflict have focused on its more conspicuous forms, including infanticide [10,11], forced copulations [12,13], and sexual harassment [14][15][16]. Pioneering studies exploring more discreet forms of sexual coercion, such as sexual intimidation in chimpanzees (Pan troglodytes), have reported that males who direct repeated aggression toward cycling females are more likely to mate with them around ovulation [17][18][19][20]. Besides this work and some anecdotal reports [7,21,22], the prevalence and evolutionary importance of sexual intimidation in wild primates remain largely unknown.…”
Section: Resultsmentioning
confidence: 99%
“…First, our results present new evidence supporting the use of sexual intimidation by wild chacma baboons. Such behavior, previously reported only in chimpanzees [17][18][19][20], may therefore occur in a wider range of primates, strengthening the case for an evolutionary origin of human sexual intimidation [2,3]. Earlier work in baboons has underlined the importance of conditioning aggression by male hamadryas baboons, typically expressed when females leave their spatial proximity [30][31][32], and has also reported higher rates of male aggression against cycling (versus non-cycling) females in chacma baboons [33][34][35][36].…”
Section: Discussionmentioning
confidence: 95%
“…Chimpanzee males form coalitions to maintain or improve their social status, and male–male aggression sometimes precipitates into serious, even lethal injuries (de Waal, ; Gilby et al, ; Kaburu, Inoue, & Nweton‐Fisher, ). In addition, chimpanzee males who are more sexually coercive to females possess higher reproductive success (Muller, Kahlenberg, Thompson, & Wrangham, : Muller, Thompson, Kahlenberg, & Wrangham, ; Kaburu & Newton‐Fisher, ; Feldblum et al, ). In bonobos, higher ranking males also have higher reproductive success, but male bonobos do not compete severely over social ranking: males seldom form coalitions within a group, and seldom injure their opponent (Surbeck et al, , c; Ishizuka et al, ; this study).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in primate societies, social grooming is important for the maintenance of social bonds [see Dunbar & Shultz, 2010 for a review; Nakamichi & Yamada, 2007; Schino et al, 2007], which are in turn critical for survival [Archie et al, 2014; Silk et al, 2010] and fitness [Silk, 2007; Silk et al, 2003, 2009]. It is also known that more socially competent adult male primates enjoy greater reproductive success [Kaburu & Newton-Fisher, 2015; Langergraber et al, 2013; Schülke et al, 2010], but that males are at a greater risk for mortality across the lifespan, particularly when they emigrate from the troop [Fedigan & Zohar, 1997; Isbell et al, 1993; Small & Smith, 1986]. Thus, if mothers can “prime” their young sons for adaptive social engagement early in life, they may be providing them with an advantage later in life that makes them more likely to survive their emigration and integration into a new troop.…”
Section: Discussionmentioning
confidence: 99%